Women’s Transition to Entrepreneurs from Professional and Managerial Careers in Organizations - Nindria Untarini; Sayyida Sayyida; Dwiarko Nugroho Seno (Binus Business Review, 2021)
Careers have different dimensions, they can be developed in an organization and in individual way. Organizationsno longer have a role in creating careers, but individuals develop careers using the organization as a tool ormedium. Changes in the external and internal environment in the organization are the basic conditions whyindividual career dares to change. The research aimed to explore senior female managers’ phenomenon that leftprofessional and managerial careers in organizations to be entrepreneurs. Structured and in-depth interviews wereconducted with 25 female entrepreneurs who had left senior manager positions at the companies. Qualitativeresearch approaches were carried out to explore what motivated female entrepreneurs to make a career transitionand how the career transition process was done. Then, the Critical Incident Technique was used to analyze thedata to get responses regarding female entrepreneurs’ perceptions of career transitions. From the results, thereare four main categories: personal, organizational life, value and integrity, and capital. Then, there are also ninesubcategories: independence and individualism, strong encouragement and family support, professional andpersonal life balance, organizational life, values, integrity, partner ties, mentor ties, and human capital. Thepersonal category causes more women to make a career transition, followed by capital, value and integrity, andorganizational life categories.